Analisis Optimasi Algoritma Klasifikasi Support Vector Machine, Decision Trees, dan Neural Network Menggunakan Adaboost dan Bagging - Agus Heri Yunial (Teknik Informatika Universitas Pamulang, 2020)
The accuracy value of a classification algorithm shows whether the algorithm is good or not in classifying data which can affect the results of the classification method in data mining processing. In this study, the author will analyze the effect of optimization using the adaboost and bagging methods on the results of the classification algorithm accuracy value on support vector machines, decision trees, and neural networks. This study uses a software in data mining processing that is using the Weka application version 3.8.1. The test method used was a percentage split of 70%. In this study, the results show that adaboost optimization can increase the accuracy value of the support vector machine algorithm from 88.93% to 89.10%, decision trees from 90.24% to 90.36%, and neural network from 88.53% to 88.61%, while bagging optimization can only increase Algortima decision trees become 90.55%, and the neural network becomes 90.38%, because the accuracy value of the support vector machine algorithm is the same as the accuracy value of bagging, which is 88.93%.